THE ROLE OF WORK ENGAGEMENT AND DECISION MAKING STYLE ON JOB CRAFTING AND IN-ROLE PERFORMANCE - Akinbobola, Olusola I. (African Journal of Social and Behavioural Sciences, 2024)
This study adopted Job Demands and Resources Decision Making model to investigate and increase understanding of decision-making processes and work engagement on job crafting and in-role performance. A cluster sampling technique was used to select 250 professionals (148 females; 102 males) involved in decision making from various industries including health care, educational, financial and engineering/information technology in a cross-sectional survey in Lagos State, Nigeria. These participants responded to structured psychological scales. Statistical Package for Social Science version 20 was used for the descriptive and correlation analysis, while Analysis of, Moment of Structure version 21 was used to perform the Structural Equation Model. All analysis was performed at *P<0.05. Job crafting significantly influenced in-role performance; decision-making style significantly influenced in-role performance. Work engagement significantly moderated the relationship between decision-making style and in-role performance such that the relationship was stronger for those high on work engagement as compared to those low on work engagement. The Job Demands and Resources Decision Making model is partially supported when it utilized heterogeneous sample involved in decision making. It also indicated opportunity for job crafting through cognitive functioning.